The General Theory and monetary policy: Investment versus inflation - Geoff Tily (Intervention. European Journal of Economics and Economic Policies, 2009)
Keynes's theory of investment and the economic cycle is set out. Against this theory it is argued that the current monetary policy framework is not credible. Rather, given its implicit endorsement of financial liberalisation, it is, and has proved, deeply dangerous. Keynes advocated policies aimed at setting a low long-term rate of interest. Financial liberalisation has led to the dear rates that Keynes understood as the cause of the Great Depression. The discussion also examines Keynes's vigilant approach to infl ation and argues that the inflation of the 1970s was connected with liberalisation not Keynes. The loss of the central role for investment and the pre-occupation with inflation in post-Keynesian economics is traced. Finally events from the golden age to the present debt-deflation are examined according to this perspective.
Keywords: B22; B50; E40; E60; 330; monetary policy; financial liberalisation; investment; inflation; debt deflation